A New Informatics Geography - Coiera, E. (Yearbook of Medical Informatics, 2016)
Introduction: Anyone with knowledge of information systems has experienced frustration when it comes to system implementation or use. Unanticipated challenges arise frequently and unanticipated consequences may follow.Objective: Working from first principles, to understand why information technology (IT) is often challenging, identify which IT endeavors are more likely to succeed, and predict the best role that technology can play in different tasks and settings.Results: The fundamental purpose of IT is to enhance our ability to undertake tasks, supplying new information that changes what we decide and ultimately what occurs in the world. The value of this information (VOI) can be calculated at different stages of the decision-making process and will vary depending on how technology is used. We can imagine a task space that describes the relative benefits of task completion by humans or computers and that contains specific areas where humans or computers are superior. There is a third area where neither is strong and a final joint workspace where humans and computers working in partnership produce the best results.Conclusion: By understanding that information has value and that VOI can be quantified, we can make decisions about how best to support the work we do. Evaluation of the expected utility of task completion by humans or computers should allow us to decide whether solutions should depend on technology, humans, or a partnership between the two.
Keywords: Human-computer interaction; utility; expected value; value of information; workaround; communication